Respiratory electron transfer pathways in plant mitochondria - Schertl, Peter; Braun, Hans-Peter (Frontiers in Plant Science, 2014)
The respiratory electron transport chain (ETC) couples electron transfer from organic substrates onto molecular oxygen with proton translocation across the inner mitochondrial membrane. The resulting proton gradient is used by the ATP synthase complex for ATP formation. In plants, the ETC is especially intricate. Besides the “classical” oxidoreductase complexes (complex I to IV) and the mobile electron transporters cytochrome c and ubiquinone, it comprises numerous “alternative oxidoreductases”. Furthermore, several dehydrogenases localized in the mitochondrial matrix and the mitochondrial intermembrane space directly or indirectly provide electrons for the ETC. Entry of electrons into the system occurs via numerous pathways which are dynamically regulated in response to the metabolic state of a plant cell as well as environmental factors. This mini review aims to summarize recent finding on respiratory electron transfer pathways in plants and on the involved components and supramolecular assemblies.